2011
DOI: 10.1017/s1041610211001013
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' perspectives on the pre-diagnostic period in early onset dementia: a long and winding road

Abstract: Background: Recognizing and diagnosing early onset dementia (EOD) can be complex and often takes longer than for late onset dementia. The objectives of this study are to investigate the barriers to diagnosis and to develop a typology of the diagnosis pathway for EOD caregivers.Methods: Semi-structured interviews with 92 EOD caregivers were analyzed using constant comparative analysis and grounded theory. A conceptual model was formed based on 21 interviews and tested in 29 additional transcripts. The identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(194 citation statements)
references
References 34 publications
4
186
0
4
Order By: Relevance
“…[21][22][23] Studies of individuals undergoing assessment (and of their carers) have revealed equivocal views about the adequacy of information supplied, 24 and concerns about clinicians' ability to identify information needs and respond effectively; 25 observations that have similarly arisen in the Netherlands. 26,27 A literature review undertaken as part of the current study, which focused on the process of disclosure of dementia diagnosis, revealed wide variability in reported practice, with theoretical 'guidelines' that did not reflect practice. 28 Disclosure was rated by primary care physicians as causing difficulties in the management of individuals with dementia, who were less likely to use the correct terminology with patients and family members than psychiatrists.…”
Section: Resultsmentioning
confidence: 95%
“…[21][22][23] Studies of individuals undergoing assessment (and of their carers) have revealed equivocal views about the adequacy of information supplied, 24 and concerns about clinicians' ability to identify information needs and respond effectively; 25 observations that have similarly arisen in the Netherlands. 26,27 A literature review undertaken as part of the current study, which focused on the process of disclosure of dementia diagnosis, revealed wide variability in reported practice, with theoretical 'guidelines' that did not reflect practice. 28 Disclosure was rated by primary care physicians as causing difficulties in the management of individuals with dementia, who were less likely to use the correct terminology with patients and family members than psychiatrists.…”
Section: Resultsmentioning
confidence: 95%
“…As opposed to the characteristic memory loss in AD, early stage FTD is predominantly characterized by personality and behavioral changes or language deficits [5]. Behavioral changes are common debut symptoms in YOD [6, 7], and often misattributed to stress or depression. However, the phenotype of AD in younger people may also diverge from what is seen in older people, with atypical presentations [8] contributing to misattribution of symptoms and prolonged time to diagnosis [2, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In a Dutch sample of 92 people living with YOD (van Vliet et al, 2011(van Vliet et al, p. 1396, it was noted that one had an unborn child at the onset of diagnosis, seven had children between 0-10 years, thirty between 11-20 years, seventy-seven between 21-30 years, and forty-eight had children over 30 years of age. Seventeen patients within this sample had a total of 23 children living at home.…”
Section: Introductionmentioning
confidence: 99%
“…Three quarters of parents who were not affected by YOD consider their children to be impacted emotionally by having a parent with YOD (Allen et al, 2009, p. 456;Luscombe et al, 1998, p. 326). There were many stresses for young people living with a parent with YOD, particularly with 'feelings of hopelessness, embarrassment and irritation' (Thompson, 2012, p. 24;van Vliet et al, 2011van Vliet et al, p.1397. Typically shame of their parents' behaviour caused social isolation, for example, where friends were not invited to their house which further impacted their relationship with their parent (Thompson, 2012, p. 24).…”
Section: Introductionmentioning
confidence: 99%